Kontribusi Ekonomi Malam Hari dalam Pengembangan UMKM di Kota Pekanbaru - Rahmah Amanda; Hevana Rachel Marbun; Elly Nielwaty (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2025)
This study analyzes the contribution of the nighttime economy to the development of micro, small, and medium enterprises (MSMEs) in Pekanbaru City, particularly the culinary sector, which dominates nighttime economic activity. This research is motivated by the increasing public consumption at night, which shapes urban economic dynamics and requires effective public governance. The research method uses a qualitative approach through literature review and in-depth interviews with nighttime MSMEs to describe business conditions and governance challenges. The analysis is based on Adam Smith's Theory of Economic Growth, emphasizing capital accumulation, population growth, and technological advancement. The results show that nighttime economic activity generates high levels of consumption, which increases MSME income and enables capital accumulation for business development and product quality improvement. Urban population growth and the use of digital technology, including social media, delivery services, and digital payment systems, contribute to expanding market reach and improving business efficiency. However, MSME development in the nighttime economy remains constrained by limited access to capital, inadequate public infrastructure, and regulatory uncertainty. This study emphasizes the need for integrated local government policies.